Good Governance, Gender Mainstreaming, and Religion - M. Roem Syibly (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
From Good Governance perspective, Indonesia has given positive contribution toward gender issues. Legally, Indonesia has fulfilled all conditions as state with good governance, but unfortunately, at the field showed that such ordinances issued were ineffective. PSI-UII’s research report has found the correlation between violence against women and religious understanding. In the field finding will give inputs to all people who concern with the issue. Several Muslim scholars already had given us some solution with interpretation toward al-Quran and Hadits, which support gender justice and equality. Government and all organization involved, have to support law and its instrument can be applied well.Keywords: governance, gender, religious interpretation.